Antibakteri Staphylococcus Aureus dari Sediaan Sabun Mandi Probiotik Kombucha Bunga Telang (Clitoria Ternatea L) Sebagai Produk Bioteknologi - Firman Rezaldi; Candra Junaedi; Retna Yulrosly Ningtias; Fernanda Desmak Pertiwi; Heny Sasmita; Ucu Wandi Somantri; Muhammad Faizal Fathurrohim (Jurnal Biotek, 2022)
The fermented kombucha flower telang (Clitoria ternatea L) is a functional probiotic drink with antibacterial properties. This study aimed to determine and test the antibacterial activity against S. aureus from the formulation of probiotic bath soap preparations fermented kombucha flower telang. This research method was carried out experimentally in an in vitro laboratory. The formulation of probiotic bath soap preparations fermented kombucha flower telang was made with varying concentrations of 20%, 30%, and 40%. The test for antibacterial activity against S. aureus bacteria used the disc diffusion method. The working procedure includes making bath soap preparations and testing the antibacterial activity of the probiotic bath soap preparations fermented kombucha telang flower. The results showed that fermented telang flower kombucha in bath soap had an overall antibacterial activity against S. aureus. The concentration of 40% was the highest in the probiotic bath soap preparations fermented kombucha telang flower with an average inhibition zone diameter of 15.5 mm. The average value of the diameter of the inhibition zone was in a strong category.